Corporate Social Responsibility and Multinational Corporation Identity: Norwegian Strategies in the Chilean Aquaculture Industry - Huemer, Lars (Journal of business ethics, 2010)
This study brings an organizational identity perspective to the debate regarding corporate social responsibility (CSR) and multinational corporations (MNCs). The basic proposition is that organizational identities warrant closer attention since they influence CSR strategies. It is further argued that a more explicit distinction between principles and practices, or between ‘being’ and ‘doing’, is needed when debating whether multiple organizational identities are required for MNCs operating in locations characterized by different stakeholder demands. In terms of identity construction, two translation processes are suggested to be pertinent; from hypernorms to organizational principles and the translation of organizational principles to practices. The first translation is relevant since ‘hypernorms’ alone do not create the distinctiveness needed for an organizational identity to develop and the second translation helps in explaining the ability to endorse local contracts.